THE DEVELOPMENT OF INTERACTIVE MULTIMEDIA WITH STEAM INTEGRATED USING ISPRING SUITE 9 ON SUBSTANCE PRESSURE TOPIC FOR VIII GRADE - Sonia - Novita; Firda Azzahra (Universe, 2023)
Learning media in digital form is an innovation in the world of education. To support education in era of industrial revolution 4.0, teachers as educators of the nation's next generation must be able to prepare and provide non-paper-based learning media. Non paper-based learning media can be used both distance learning and face-to-face learning. One of the non paper-based learning media is interactive multimedia. This research aims to produce interactive multimedia with STEAM integrated using ispring suite 9 on substance pressure topic that is valid and practical for grade VIII students. This research uses the Research and Development (R&D) method which two stages of the Ploomp model, namely the preliminary research, and development stage or the prototyping stage with Tessmer's formative evaluation is self evaluation, expert review, one-to-one evaluation and small group evaluation. The results of the study obtained validity value is very valid category with a percentage of 90,385%. The practicality score obtained by the teacher with a percentage of 98,78% and by the students with a percentage of 93,16% is the very practical category.